2023
DOI: 10.1038/s41598-023-31732-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant activity in various spirulina containing products and factors affecting it

Abstract: Spirulina is a popular food supplement known for its high antioxidant activity. Several studies have shown that antioxidant activity fluctuates depending on the combination of ingredients in the food. Fresh spirulina is a growing market trend; however, pure spirulina short shelf life is a strong limitation. This study aims to investigate antioxidant activity of various novel commercial fresh spirulina-containing products and the factors affecting it. Antioxidant activity and total phenolic content of each ingr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The data, reported in Table 6, showed that although comparable results between the two different extractions were found through FRAP analysis (although statistically higher for the extract in PBS in comparison to the MetOH 80% extract), ABTS •+ failed to find such values following lipophilic extraction in MetOH 80%. Therefore, as already reported in the literature [22], hydrophilic PBS extraction is confirmed as the most suitable for determining the TAC of spirulina samples. Spirulina as a dietary supplement is known for its high antioxidant power [2].…”
Section: Total Antioxidant Capacity (Tac) Of Spirulina Samples Extrac...supporting
confidence: 74%
See 1 more Smart Citation
“…The data, reported in Table 6, showed that although comparable results between the two different extractions were found through FRAP analysis (although statistically higher for the extract in PBS in comparison to the MetOH 80% extract), ABTS •+ failed to find such values following lipophilic extraction in MetOH 80%. Therefore, as already reported in the literature [22], hydrophilic PBS extraction is confirmed as the most suitable for determining the TAC of spirulina samples. Spirulina as a dietary supplement is known for its high antioxidant power [2].…”
Section: Total Antioxidant Capacity (Tac) Of Spirulina Samples Extrac...supporting
confidence: 74%
“…For TAC, considering the low ability of the polar solvent EtOH in isolating the antioxidant compounds of spirulina as previously shown in the paper by Stunda-Zujeva et al [22], MetOH 80% was chosen as polar solvent and for the first time compared to phosphatebuffered saline (PBS) to extract the lipophilic and hydrophilic component, respectively. In particular, samples were extracted according to Molinari et al [23], for the lipophilic component.…”
Section: Extraction Process For Total Antioxidant Capacity (Tac) Dete...mentioning
confidence: 99%
“…The presence of active compounds such as phycocyanin and beta-carotene in spirulina contributed to its strong antioxidant potential. In a study, Stunda-Zujeva et al [40] stated that phycocyanin is the main antioxidant of spirulina, offering various uses for health benefits, although care should be taken in terms of the antioxidant activity, which fluctuates. Numerous studies have highlighted the higher antioxidant capacity and beneficial fatty acid profiles, including higher concentrations of omega-3 polyunsaturated fatty acids, in both microalgae species compared to control groups.…”
Section: Discussionmentioning
confidence: 99%
“…As it is significantly decreased in the serum AST, ALT, and ALP levels, Spirulina might prevent hepatic enzymes from leaking to blood stream. This protective effect of Spirulina is linked to the repair or prevention of hepatic tissue damage and may be an outcome of plasma membrane stabilization, as Spirulina has substantial antioxidant activity and stimulates a free radical scavenging enzyme system (Stunda-Zujeva et al, 2023). Furthermore, Mazo et al (2004) have shown that the presence of -carotene in Spirulina may have this protective impact, and Spirulina is regarded as a source of some macro-and micronutrients such as vitamins, linolenic fatty acids, proteins, carotenoids and iron (Weber et al, 2003).…”
Section: Liver Enzymes Activity Alanine Transaminase Enzyme Activity ...mentioning
confidence: 99%